Simulations of large-scale zero boiloff, densification, and solidification of hydrogen - Colin P. Mahony; Jeffrey G. Marchetta; Adam M. Swanger (Results in Engineering)
An Integrated Refrigeration and Storage (IRAS) experimental system called the Ground Operations and Demonstration Unit for Liquid Hydrogen (GODU-LH2) demonstrated the ability store cryogens in a zero boiloff (ZBO) process, and to densify liquid hydrogen by reducing the temperature and pressure down to the triple point resulting in solidification. The incompressible Navier-Stokes was utilized to simulate ZBO, densification, and solidification of liquid hydrogen (LH2) in the IRAS tank. The simulations were performed using a commercially available Computational Fluid Dynamics (CFD) pressure-based mass and momentum flow model and an enthalpy-porosity energy model. Results demonstrated the simulation's ability to predict time-dependent flow and temperature fields and solid-liquid phase locations for hydrogen during ZBO, densification, and solidification. The simulations showed good agreement with experimental data, with errors within acceptable ranges for temperature and pressure predictions, provided detailed insights into natural convection and solid-liquid phase change dynamics. These findings are critical for the design of future cryogenic fluid management systems.